Tinjauan Hukum Terhadap Kejahatan Online Scamming sebagai Bentuk Kejahatan Kontemporer - Fatmawaty Fatmawaty; Rusman Malik (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of information technology and internet-based communication has significantly transformed various aspects of human life, particularly in the fields of commerce, finance, and social interaction. Along with these advancements, cybercrime has emerged as a growing threat, one of which is online scamming. Online scamming refers to fraudulent activities conducted through electronic media or digital platforms with the intention of deceiving victims for financial gain. This form of crime has become increasingly sophisticated through various methods, including phishing, love scams, online shop scams, investment scams, impersonation scams, and social engineering. The borderless nature of cyberspace, the anonymity of offenders, and the complexity of digital evidence present significant challenges for law enforcement agencies. This study aims to analyze online scamming as a contemporary crime, examine the legal framework governing online scamming in Indonesia, and evaluate the effectiveness of law enforcement efforts in addressing such offenses. The research employs a normative legal method using statutory, conceptual, and case approaches. The legal materials consist of primary legal sources, including the 1945 Constitution of the Republic of Indonesia, the Criminal Code (KUHP), and Law Number 1 of 2024 concerning the Second Amendment to the Electronic Information and Transactions Law (ITE Law), supported by secondary and tertiary legal materials. The findings indicate that online scamming fulfills the elements of fraud under the Criminal Code and may also be prosecuted under the ITE Law and other relevant regulations, including the Personal Data Protection Law. However, challenges remain in law enforcement due to technological advancements, transnational criminal networks, difficulties in tracing digital assets, and limited public awareness regarding cybercrime. Therefore, effective prevention and eradication of online scamming require not only penal measures through criminal law enforcement but also non-penal approaches, such as enhancing digital literacy, strengthening cybersecurity systems, and promoting international cooperation in combating cybercrime.